Security and Privacy Enhancement in Decentralized Digital Data Sharing Environments - Muhamad Yusup; Mardiana; Ageng Setiani Rafika; Putra Wahyudi, Otniel Feliks; Agung Lorenzo (Pandawan, 2026)
This study examines the suitability of the IPFS as a decentralized architecture for secure digital data exchange. Traditional centralized protocols, such as HTTP, introduce structural vulnerabilities, including single points of failure, metadata exposure, and susceptibility to interception or unauthorized modification. As digital data exchange becomes increasingly essential in various sectors, ensuring data security and privacy has become a growing concern. The primary objective of this study is to evaluate IPFS’s ability to address these vulnerabilities and enhance the security and privacy of digital data-sharing environments. This research employs a structured literature review to synthesize findings from distributed-systems research, cryptographic studies, and peer-to-peer networking analyses. Additionally, the study benchmarks IPFS against traditional storage protocols, such as HTTP and FTP, to assess its advantages and limitations. The results demonstrate that IPFS offers significant advantages, including content-addressed storage, Merkle-DAG verification, and decentralized peer replication. These features improve fault tolerance, ensure data integrity, and reduce the risks of data tampering. However, limitations, such as content availability and reliance on node uptime, are also noted. While IPFS is not a complete security solution, it provides a strong foundational architecture for privacy-preserving, distributed data-sharing workflows when paired with complementary cryptographic and governance frameworks, making it a viable alternative for secure digital data exchange.